The Impact of the One Price Fuel Oil (BBM) Program on the 3T Rural Economy in Indonesia - Firdaus, Firdaus Adam; Hartono, Djoni (Universitas Negeri Semarang, 2025)
The One Price Fuel Policy is a positive step to reduce fuel price inequality throughout Indonesia. In the 6years of implementing this program (2017-2022), the BBM Distribution Business Entity has built 423distributors throughout Indonesia. The success of the One Price Fuel program is still being debated. So thisresearch wants to examine further the influence of one-price fuel on the rural economy in the 3T region ofIndonesia with a research focus on the number of small industries and economic facilities includingmarkets, supermarkets, grocery stores, food stalls, restaurants, and hotels. Researchers used a Differencein Difference (DiD) regression model with a staggered events approach and two strategies to control non-intervention factors that influenced the results. This research found that in certain case scenarios, thispolicy was implemented gradually after one year of implementation, causing a causal impact on thenumber of grocery stores and food stalls, and in other outcomes, the results could not be validated becausethe assumptions had not been met.